Prognostic impacts of left ventricular strain in hemodialytic patients with preserved left ventricular systolic function - Fu, Yi-Tsang; Tseng, Chih-Hsueh; Huang, Wei-Min; Yu, Wen-Chung; Cheng, Hao-Min; Chiang, Chern-En; Chen, Chen-Huan; Sung, Shih-Hsien; Lin, Chih-Ching (Scientific reports, 2025)
Left ventricular dysfunction is a known risk factor for morbidity and mortality in hemodialysis patients. The prognostic value of left ventricular global longitudinal strain (LV GLS) among those with preserved left ventricular ejection fraction (LVEF) remains uncertain. Subjects with end-stage renal disease initiated hemodialysis at Taipei Veteran General Hospital between 2015 and 2018 were registered. All participants received annually echocardiographic studies thereafter. Left ventricular end-systolic volume (LVESV), end-diastolic volume (LVEDV) and internal diameter in systole (LVIDs), LVEF, and LV GLS were measured. A LV GLS of > – 15.9% was defined as reduced LV GLS. Clinical outcomes of mortality and hospitalization for heart failure (HHF) were followed. A total of 319 patients with preserved LVEF (66.3 ± 15.1 years, 48.6% men) were recruited in the study. Subjects with reduced LV GLS had more coronary artery disease (CAD), higher LVESV and LVIDs, but were similar in age, gender, co-morbidities, biochemistries and other echocardiographic parameters as the counterpart. Both CAD [(odds ratio (OR) and 95% confidence intervals (CIs): 1.669, 1.023–2.724], and LVESV (OR per-1 mL and 95% CIs: 1.073, 1.004–1.146) were independent determinants of reduced LV GLS. Kaplan-Meier analysis indicated that patients with reduced LV GLS had a significantly lower event-free survival rate compared to those with preserved GLS. The multivariate Cox regression analysis further demonstrated LV GLS as a significant predictor of adverse clinical events (hazard ratio per-1% and 95% CIs: 1.055, 1.002–1.110) after accounting for age, gender, and diabetes. Among the hemodialysis patients with preserved LVEF, LV GLS but not the conventional left ventricular functional indices were associated with long-term mortality and HHF. CAD could be a modifiable risk factor among the subjects with reduced LV GLS.